Comparative effectiveness of school-based exercise interventions on physical fitness in children and adolescents: a systematic review and network meta-analysis - Wu, Jin; Yang, Yuhang; Yu, Huasen; Li, Liqiang; Chen, Yanying; Sun, Youping (Frontiers in Public Health, 2023)
BACKGROUND: Schools provide a favorable setting for health education, however, the most effective school-based exercise mode for improving physical fitness remains unclear. This network meta-analysis was designed to assess and rank the comparative efficacy of six exercise modalities on physical fitness indicators in a school-based setting. METHODS: An online search of the Web of Science, PubMed, SportDiscus, and Scopus databases was conducted. Randomized and quasi-randomized controlled trials were considered. Outcomes included measures of anthropometry and body composition, muscular fitness, and cardiorespiratory fitness. Data were pooled with a random effects model using the frequentist framework. RESULTS: A total of 66 studies with 8578 participants (48% girls) were included. High-intensity interval training was the most effective intervention reducing body mass index (mean difference (MD) = -0.60 kg·m-2, 95% confidence interval (95%CI) = -1.04 to -0.15, P = 0.009), elevating VO2max (MD=3.59 mL·kg−1·min-1, 95% CI= 2.45 to 4.74, P < 0.001), and 20-meter sprint performance (MD = -0.35 s, 95% CI = -0.55 to -0.14, P = 0.001). Aerobic training had the highest probability of reducing waist circumference (standardized mean difference (SMD) = -0.60, 95% CI = -0.88 to -0.32, P < 0.001). Active video games emerged as a promising modality for improving countermovement jump (MD = 2.43 cm, 95% CI = 0.06 to 4.80, P = 0.041) and shuttle running performance (SMD = 0.86, 95% CI = 0.29 to 1.43, P = 0.003). Strength training was the best exercise mode for improving standing long jump performance (SMD = 1.03, 95% CI = 0.07 to 1.98, P = 0.035) while combined training was rated the first for decreasing body fat percent (MD = -2.56%, 95% CI = -4.73 to -0.40, P = 0.022) and increasing push-up repetitions (SMD = 3.59, 95% CI = 0.81 to 6.37, P = 0.012). CONCLUSIONS: School-based exercise interventions have multiple effects on physical fitness. The findings of this study will help to inform physical education teachers and coaches how best to deliver exercise programs in a school setting. Since the study was limited by the original research, the conclusions will require further verification using high-quality randomized controlled trials.